An experimental investigation of interspecies variation in mechanical properties of cortical bone - Welgemoed, Lee-Anne (Department of Mechanical Engineering, 2019)
Cortical bone has been found to display properties that vary greatly, with most previous work focused on human or bovine bone. The main aim of this research was to investigate mechanical properties of cortical bone from various species of animal (ostrich, baboon, crocodile and sheep) to allow for comparison of mechanical properties across species, as well as investigate the relationship of material properties to strain rate within each species. This information is valuable for use in modelling. Testing was performed quasistatically and at the high end of the intermediate strain rate regime. These higher rate tests were performed on a modified Split Hopkinson bar setup. A Cone-in-Tube striker was used to provide a near constant strain rate during testing. The use of a momentum trapping system was investigated, but was not practically useful for the scale of specimens and strain rates investigated. It was found that properties of bone from all species displayed a clear dependence on strain rate. The relationship between the properties and strain rate were very similar across all species investigated, although the ultimate values differed. The apparent modulus showed a distinct increase when testing at a higher strain rate than when testing quasistatically. The compressive strength (both yield and ultimate) displayed an increase over the quasistatic range tested and then levelled out at the higher rate. There was greater difference seen in the values of apparent modulus than in the compressive strengths for all species tested. Baboon bone consistently displayed the greatest properties for both apparent modulus and compressive strength, and crocodile the weakest. It was also found that, despite whole bones and specimens being frozen at -32◦C, with the specimens frozen in normal saline, a change in the material properties of the bone occurred over time. Apparent moduli decreased, and compressive strengths stayed constant or increased slightly. Less change was seen in the strength than in the apparent modulus.